A review of epidemiological models of Clostridioides difficile transmission and control (2009–2021). (April 2022) - Lanzas, Cristina; Jara, Manuel; Tucker, Rachel; Curtis, Savannah
Abstract: Clostridioides difficile is the leading cause of infectious diarrhea and one of the most common healthcare-acquired infections worldwide. We performed a systematic search and a bibliometric analysis of mathematical and computational models for Clostridioides difficile transmission. We identified 33 publications from 2009 to 2021. Models have underscored the importance of asymptomatic colonized patients in maintaining transmission in health-care settings. Infection control, antimicrobial stewardship, active testing, and vaccination have often been evaluated in models. Despite active testing and vaccination being not currently implemented, they are the most commonly evaluated interventions. Some aspects of C. difficile transmission, such community transmission and interventions in health-care settings other than in acute-care hospitals, remained less evaluated through modeling. Highlights: A systematic search and bibliometric analysis of mathematical and computational models for Clostridioides difficile transmission identified 33 publications from 2009 to 2021. Most studies focus on C. difficile transmission in acute-care hospitals in high-income settings and the most evaluated interventions were vaccination and active testing. Very few models address transmission of C. difficile in nursing homes, long-term care facilities, and at community level.